Prenatal presentation and postnatal evolution of a patient with Jansen metaphyseal dysplasia with a novel missense mutation in PTH1R. Issue 10 (15th August 2013) - Savoldi, Gianfranco; Izzi, Claudia; Signorelli, Marino; Bondioni, Maria Pia; Romani, Chiara; Lanzi, Gaetana; Moratto, Daniele; Verdoni, Lucio; Pinotti, Moira; Prefumo, Federico; Superti‐Furga, Andrea; Pilotta, Alba
ABSTRACT Wave‐shaped ribs were detected at prenatal ultrasound in a 20+1 week female fetus. At birth, skeletal radiographs showed marked hypomineralization and suggested hypophosphatasia. However, elevated blood calcium and alkaline phosphatase excluded hypophosphatasia and raised the possibility of Jansen metaphyseal dysplasia. Molecular analysis of the PTH/PTHrP receptor gene (PTH1R) showed heterozygosity for a previously undescribed transversion variant (c.1373T>A), which predicts p.Ile458Lys. In vitro evaluation of wild type and mutant PTH/PTHrP receptors supported the pathogenic role of the p.Ile458Lys substitution, and confirmed the diagnosis of Jansen metaphyseal dysplasia. This disorder may present prenatally with wavy ribs and in the newborn with hypomineralization, and may therefore be confused with hypophosphatasia. The mottled metaphyseal lesions typically associated with this disease appear only in childhood. © 2013 Wiley Periodicals, Inc.